Angioma serpiginosum: report of an unusual acral case and review of the literature - Azael Freites-Martinez; Amalia Moreno-Torres; Almudena Hernández Núñez; Diego Martinez-Sanchez; Maria Huerta-Brogeras; Jesus Borbujo (Sociedade Brasileira de Dermatologia, 2015)
AbstractWe report the case of a 35-year-old woman with deep-red asymptomatic macules on the plantar and dorsal skin of the right great toe. Histopathologic fi ndings were compatible with Angioma serpiginosum. Immunohistochemical stains for estrogens and progesterone receptors were negative. Dermoscopy showed an erythematous parallel ridge pattern with double rows of irregular dots and globules. We report an unusual case of angioma serpiginosum with acral volar skin involvement. The dermoscopic features described may aid in the diagnosis of AS in this specifi c skin area. Acral volar skin involvement must be included in the clinical spectrum of Angioma serpiginosum and in the differential diagnosis of acral vascular lesions.